Impact response of novel layered two stage fibrous composite slabs with different support type. (February 2021) - Rithanyaa, R.; Murali, G.; Salaimanimagudam, M.P.; Fediuk, Roman; Abdelgader, Hakim S.; Siva, A.
Abstract: The performance of novel Layered Two Stage Fibrous Composite slabs (LTSFC) was pioneered under falling mass collisions using a combined experimental and numerical study. Such LTSFC slabs consist of three layers with and without the insertion of glass fibre mesh between the layers. LTSFC techniques were used to fabricate the composite slabs with three layers including 3%, 1.5%, and 3% of fibre content for the top, middle, and bottom layers respectively. Sixteen MLPAFC square slabs were cast with only short hooked end fibres and tested under falling mass collisions by amending two parameters namely the type of support (fixed and hinge) and support layout. Two distinct support layouts on two types of support were considered and tested with and without the glass fibre mesh between layers of LTSFC. A glass fibre mesh was introduced between the three layers to block crack growth propagation and absorb additional collision energy. The glass fibre mesh insertion between the layers and the LTSFC production technique were considered as novel modifications. A numerical study using Auto desk Fusion 360 was conducted and compared with experimental results. The numerical results showed fair agreement with the experimental test results. Based on the validated numerical models, collision energy and cracking pattern evolution were studied. The findings indicated that the glass fibre mesh insertion between the layers combined with steel fibres disrupted crack proliferation, thus exhibiting superior engrossed collision energy and postponing crack growth. Additionally, the engrossed collision energy at crack initiation and ultimate crack for the slabs with four sides fixed and hinged support were greater with respect to two opposite sides fixed and hinged support. Numerical values were in reasonable agreement with the experimental values in terms of collision energy and cracking patterns.